Beyond Geographical Barriers: ICT Skills and Parental Involvement in Fostering Learning Independence - Lukmana, Dana Arif; Sapil, Nursin; Maulida, Ulfa (International Journal of Trends in Mathematics Education Research, 2024)
This study analyses the links between students' Information and Communication Technology (ICT) abilities, parental role, and learning Independence in North Maluku, an archipelagic region of Indonesia characterized by poor technical infrastructure. By implementing a quantitative, cross-sectional approach, data were collected from 303 high school students using validated measures of ICT abilities, parental involvement, and learning independence. Multiple regression research found that ICT skills and parental role combined account for 44% of the variance in learning independence. ICT abilities emerged as a robust predictor (β = .464, p .001) of learning independence, underlining the essential significance of digital literacy in supporting autonomous learning practices, particularly in technologically impoverished locations. The parental role also revealed a substantial impact (β = .295, p .001), showing the persistent importance of family support in the educational process, especially in technology-enhanced learning contexts. These findings have substantial implications for educational policy and practice in archipelagic and technologically challenged countries, highlighting the necessity for focused ICT skill development programs and attempts to improve parental involvement in technology-mediated learning.